(untitled) (Applied Biological Research, 2023)
The identification and classification of bamboos based on morphological characters is a quite difficult task due to long and irregular flowering, lack of sufficient distinguished morphological characters and environmental influence. The present study was aimed to elucidate the phylogenetic relation ship between the species of tribe Bambuseae and Arundinarieae based on maturase K (matK) as a candidate gene marker. Fifteen bamboo species matK genes were sequenced and their accession numbers (OM57488 to OM417520) generated from NCBI along with matK gene sequences of additional bamboo species including the outgroup species retrieved from Gene Bank to infer the phylogenetic relationship. The phylogenetic tree of Maximum Liklihood (ML) and Maximum Parsimony (MP) revealed that the bamboo species of tribe Bambuseae and Arundinarieae were clustered in separate clades, with some exceptions. TheMLtree showedaclose relationship between Ochlandrae bracteata and Schizostachyum polymorphum with 96% bootstrapping support. Similarly, Bambusa assamica, Gigantochloa atroviolacea and Bambusa polymorpha; and B. oliveriana, B. wamin and B. nutans showed sister relation ships. Clade-II showed the group of species of tribe Arundinarieae, except Schizostachyubrachycladum and Gignatochloa rostrata, the Phyllostachys nidularia and Phyllostachys aureosulcata seem to be recently evolved. The MP tree showed association between Schizostachym polymorphum and Ochlandrae bracteata with 91% bootstrapping support, while, Gigantochloa atroviolacea and B. assamica exhibited close association with 97% bootstrapping support. The inferences from the phylogenetic trees and DNA polymorphism analysis that matK gene possessed moderate revolutionary potential for species discrimination, for better phylogerevealed netic resolution. The multigene barcode approach along with phenotypic observations need to be considered.